2014
DOI: 10.5812/numonthly.19598
|View full text |Cite
|
Sign up to set email alerts
|

Post Cardiac Surgery Acute kidney Injury: A Woebegone Status Rejuvenated by the Novel Biomarkers

Abstract: Background:Acute kidney injury (AKI) is common after cardiac surgery, the incidence varying between 7.7% and 28.1%. It significantly increases morbidity and mortality. Creatinine considerably delays the diagnosis with its own attended demerits. Novel urinary biomarkers are emerging which help in rapid diagnosis thus reducing the morbidity and mortality. Biomarkers of our study were neutrophil gelatinase-associated lipocalin (NGAL) and Interleukin-18 (IL-18).Objectives:To find out the incidence of AKI in post-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…It is produced by macrophage cells (monocyte) and bind to IL18 receptor to induce its action which is cell mediated immunity (Gami and Garovic, 2004). Previous studies reported that IL-18 is specific for renal tubules as its level increased with ischemic reperfusion injury (Faubel and Edelstein, 2005) and increased in AKI patients for being superior to serum creatinine in early detection (Jayaraman et al, 2014). Haase et al (2008) attributed its increased levels for being non-specific marker that was associated with systemic inflammation rather than damage of renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…It is produced by macrophage cells (monocyte) and bind to IL18 receptor to induce its action which is cell mediated immunity (Gami and Garovic, 2004). Previous studies reported that IL-18 is specific for renal tubules as its level increased with ischemic reperfusion injury (Faubel and Edelstein, 2005) and increased in AKI patients for being superior to serum creatinine in early detection (Jayaraman et al, 2014). Haase et al (2008) attributed its increased levels for being non-specific marker that was associated with systemic inflammation rather than damage of renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Oliguria and AKI during aortic surgery have multifactorial etiology [1,7]. Incidence of AKI during thoracoabdominal aortic aneurysm surgery ranges from 7.7% to 28% higher than other surgery [2]. Since hypovolemia and renal hypoperfusion is prone to occur by CPB pump in thoracoabdominal aortic aneurysm surgery, anesthesiologist is more likely to think of pre-renal factor when oliguria occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of AKI during thoracoabdominal aortic aneurysm surgery ranges from higher than other surgery [2]. One of the reasons why AKI commonly occurs during thoracoabdominal aortic aneurysm surgery is that hypovolemia and renal hypoperfusion may result from aortic clamping and Cardiopulmonary Bypass (CPB) pump.…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have reported that urinary N-GAL is specific and sensitive in predicting AKI 1 h after CPB [69]. This biomarker has also been tested to discriminate prerenal from intrinsic AKI [70].…”
Section: Biomarkers Of Akimentioning
confidence: 98%
“…The interleukin (IL)-6 [71] and IL-18 [70], expression of systemic inflammatory response, produced by proximal renal tubules, have also been investigated. The TRIBE (Translational Research Involving Biomarkers and Endpoints) study [72] recently validated the clinical predictivity of plasma N-GAL and urine IL-18 in estimating postcardiac surgery AKI and relative outcomes, with an area under the curve of 0.75 and 0.76, respectively.…”
Section: Biomarkers Of Akimentioning
confidence: 99%